2014
DOI: 10.4236/ijg.2014.54039
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Intra-Annual Variability of Precipitation Based on Geostatistics. A Case Study for the Paraiba Do Sul Basin, Southeastern Brazil

Abstract: The emphasis in this research is to evaluate the spatial distribution of the precipitation using a geostatistics approach. Seasonal time scales records considering DJF, MAM, JJA e SON periods performed the analysis. Procedures to evaluate the variogram selection and to produce kriging maps were performed in a GIS environment (ArcGIS ®). The results showed that kriging method was very suitable to detect both large changes in the whole area as those local small and subtle changes. Kriging demonstrated be a power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
3
6
0
3
Order By: Relevance
“…For the past period, simulated point precipitation rates indicate a variation of up to 74.1% for the annual mean, while in the summer period, this variation reaches 99.8%. These results also agree with those obtained by Silva and Simões (2014) when analyzing the spatial distribution of the observed rainfall for the Paraíba do Sul watershed region.…”
Section: Resultssupporting
confidence: 90%
“…For the past period, simulated point precipitation rates indicate a variation of up to 74.1% for the annual mean, while in the summer period, this variation reaches 99.8%. These results also agree with those obtained by Silva and Simões (2014) when analyzing the spatial distribution of the observed rainfall for the Paraíba do Sul watershed region.…”
Section: Resultssupporting
confidence: 90%
“…The average precipitation for the future period (2011-2040) is 1456.3mm, and the irregular distribution of precipitation is persistent for the analyzed period, demonstrating that the formation of the irregular relief, with the presence of mountains and hills (AB'SABER, 2003), generates a spatial irregularity in the distribution of precipitation, results that are similar to those obtained by Silva and Simões (2014). The simulation points with the highest precipitation values were, respectively, the grids P10, P2, P7 and P6, where the minimum average precipitation value was 1027.5mm and the maximum was 1856.5mm, with a variation of 44.6% between precipitation extremes, values that are similar to results from Santos and Fisch (2016).…”
Section: Precipitation Comparison Between Past and Future Periodssupporting
confidence: 79%
“…Long-term assessment of water resources is highly unpredictable (Silva and Simões, 2014), and previous studies have shown a bimodal pattern of annual cycle precipitation with dry and wet seasons clearly defined. Folhes and Fisch (2006) quantified the ratio between winter and summer rainfall in relation to the annual precipitation; the values were 8 and 42%, respectively, though the wet rainy period, from spring (Oct) to summer (March), can reach values close to 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Folhes and Fisch (2006) quantified the ratio between winter and summer rainfall in relation to the annual precipitation; the values were 8 and 42%, respectively, though the wet rainy period, from spring (Oct) to summer (March), can reach values close to 70%. Figure 2, extracted from Silva and Simões (2014), represents the spatial distribution of the rainfall at the Paraíba do Sul watershed. The highest average precipitation is concentrated in the western part (corresponding to the Serra da Mantiqueira Ridge, with altitudes close to 2400 m) and the northeastern portion (corresponding to the Bocaina Plateau, with altitudes of approximately 1400 m).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation